Impact of smoking on guided tissue regeneration using a biocomposite poly (lactic-co-glycolic) acid/sub-micron size hydroxyapatite with a rubber dam as an alternative barrier. (March 2015) - Stramazzotti, D; Coiana, C; Zizzi, A; Spazzafumo, L; Sauro, S; D'Angelo, AB; Rubini, C; Aspriello, SD
The purpose of our study was to critically evaluate the results obtained from a guided tissue regeneration technique after 12 months using a bocomposite poly (lactic-co-glycolic) acid/sub-micron size hydroxyapatite (PLGA/HA) with a rubber dam as a barrier in smoking and non-smoking patients. We selected 36 patients (18 current smokers and 18 non-smokers) diagnosed with chronic advanced periodontitis with a periodontal site (probing depth [PD] >5) amenable to regenerative surgery. Twelve months after surgery, the periodontal parameters were found to have statistically improved, when non-smokers were compared with smokers, in: PD reduction (6.3 ± 2.1 mm vs. 3.6 ± 1.9 mm); CAL gain (4.4 ± 1.1 vs. 2.8 ± 2.2 mm); recession (1.8 ± 1.4 mm vs. 0.8 ± 0.9 mm); and hard tissue fill (4.7 ± 0.8 mm vs. 2.8 ± 2.1 mm). Furthermore, since we found PD baseline differences between groups, smoking seemed not to influence the outcomes achieved (CAL gain and ΔREC) 12 months post surgery with respect to PD baseline. The use of PLGA/HA with a rubber dam significantly improved the periodontal parameters in both smoking and non-smoking subjects. This improvement was nevertheless lower in smokers than the non-smokers, confirming the negative impact of smoking on periodontal regeneration.